Defining distinct features of anti-MOG antibody associated central nervous system demyelination - Weber, Martin S.; Derfuss, Tobias; Metz, Imke; Brück, Wolfgang (Therapeutic advances in neurological disorders, 2018)
Extensive research over the last decades basically failed to identify a common cause of noninfectious inflammatory central nervous system (CNS) demyelinating disease. To a great extent, this may reflect that the group of inflammatory CNS demyelinating disorders likely contains multiple pathogenetically distinct disease entities. Indeed, the greatest success so far in deciphering the pathogenesis of a CNS demyelinating disorder resulted from the discovery of anti-aquaporin (AQP)-4 antibodies (ab), which allowed progressive delineation of neuromyelitis optica (NMO), formerly considered a variant of the most common CNS demyelinating disorder, multiple sclerosis (MS), as a distinct disease. Nowadays, AQP-4+ NMO is considered an autoimmune astrocytopathy, in which CNS demyelination occurs only as a consequence of a primary destruction of astrocytes. Delineating these patients concomitantly revealed that not all patients presenting with clinically NMO-suggestive disease phenotype express AQP-4 ab, which created the pathogenetically undefined category of NMO spectrum disorders (NMOSD). Recent investigations discovered that a subgroup of these AQP-4– NMOSD patients produce an ab response against myelin oligodendrocyte glycoprotein (MOG), a molecule expressed on the outer lamella of the myelin sheath. Using pathophysiologically meaningful cell-based assays, this humoral response is extremely rare in adult MS and absent in classical AQP-4+ NMO, sharply differentiating the evolving group from both established disorders. In this review, we summarize available clinical, immunological and histopathological data on patients with MOG+ CNS demyelinating disease. By comparing this clearly distinct cohort to AQP-4+ NMO as well as MS, we propose that MOG+ CNS demyelinating disease represents a distinct novel disease entity. In addition to its diagnostic value, we furthermore provide mechanistic insight on how this peripheral anti-MOG ab response may be of pathogenetic relevance in triggering acute flares of inflammatory CNS demyelination.